2012
DOI: 10.4314/sajas.v42i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-antibiotic feed additives on performance, immunity and intestinal morphology of broilers fed different levels of protein

Abstract: In order to investigate the effects of the dietary supplementation of organic acids, prebiotics and probiotics on broiler chickens, a total of 288 day-old male Cobb chicks were allocated in a completely randomized design according to a 2 × 4 factorial, consisting of two levels of crude protein (recommended or low (85% of recommended)) and a four feed-additive programme. The basal diet without any feed additive served as control and one of the following additives, organic acids, a prebiotic and a probiotic, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 27 publications
(38 reference statements)
7
37
0
3
Order By: Relevance
“…In a study by Timmerman et al (2006), it was reported that the positive effects of probiotics on highperformance broilers were lower than in low-performing birds. Houshmand et al (2012), in agreement with the results of Hernandez et al (2006), did not find positive effects of organic acid (formic acid) on performance. In this study, body weight gain was significantly affected by organic acid in the starter phase.…”
Section: Resultssupporting
confidence: 82%
“…In a study by Timmerman et al (2006), it was reported that the positive effects of probiotics on highperformance broilers were lower than in low-performing birds. Houshmand et al (2012), in agreement with the results of Hernandez et al (2006), did not find positive effects of organic acid (formic acid) on performance. In this study, body weight gain was significantly affected by organic acid in the starter phase.…”
Section: Resultssupporting
confidence: 82%
“…Several studies have demonstrated the importance of organic acids such as humic acid in the immune response of birds. Abdel-Fattah et al (2008), Ghazala et al (2011), andHoushmand et al (2012) observed that birds fed an organic acid-supplemented diet had heavier immune organs (bursa of Fabricius and the thymus) and a higher level of globulin in their serum, which is an indicator of immune response. Although broiler chickens in the control had some reduction in thymic volume units and the follicles of the bursa of Fabricius, this was not a manifestation of lymphocytic depletion of the thymus and bursa of Fabricius.…”
Section: Discussionmentioning
confidence: 99%
“…Lessard et al (1995) found that S. Typhimurium-infected birds had higher antibody titres in response to Newcastle disease vaccination compared with uninfected birds. Houshmand et al (2012) concluded that the dietary addition of organic acids significantly increased the antibody titres against Newcastle disease compared with the control group. The mean weight of organs as a percentage of carcass weight is documented in Table 6.…”
Section: Resultsmentioning
confidence: 99%